(untitled) (Research, Society and Development, 2022)
A properly and continuously trained nursing team is indispensable to have the therapeutic success and recovery of patients who have undergone Percutaneous Intervention (PI). Nurses should know the procedures, benefits, risks and complications, to guide their care based on nursing actions that seekto ensure quality care, avoiding adverse events related to PI. The general objective of the study is to describe the main causes of hematomas in patients after the hemodynamic procedure. Describe the complications of a hematoma in patients who underwent hemodynamic procedures, the possible causes of hematomas, analyze the nursing care that was performed for prevention before the surgical procedure and identify nursing care for patients who developed hematomas. Methodology: literature review that gathered evidence to answer the research question: what is the rate of complications related to hematomas after performing percutaneous interventions in hemodynamic procedures? Hemodynamics services are highly complex sectors that require trained and trained professionals. The nursing team plays a fundamental role in preventing complications after percutaneous intervention, the position in which the patient should remain "supine position", the time to walk after removal of the introducer sheath and the use of arterial occlusion devices the most used "compressive dressing, these three cares are fundamental in the prevention of bleeding and hematoma.